Larvicidal activity of plant extracts by inhibition of detoxification enzymes in Culex pipiens - Habeeb M. Al-Solami (Journal of King Saud University: Science, 2021)
Objectives: Plant extracts have been a safe and eco-friendly substituent of chemical pesticides, used against mosquitoes to prevent vector-borne infections e.g., chikungunya, yellow fever, dengue, filariasis, dirofilariasis tularemia, malaria, and many other diseases. Methods: The larvicidal activities of the acetone extracts of four plants e.g., Lantana camara, Ruta chalepensis, Rhazya stricta, and Acalypha fruticosa was evaluated against Culex pipiens. The composition secondary metabolites of the most effective extract (L. camara) was examined using gas chromatography-mass spectrometry (GC–MS). The expression level of Acetylcholinesterase (AChE) and Glutathione S-transferase (GST) genes were assessed through qRT-PCR. Results: The results revealed that the extract of L. camara caused 98% mortality in Cx. pipiens followed by R. stricta (91%), A. fruticosa (79%), and R. chalepensis (69%) as compared to azadirachtin, used as a positive control. The results showed that LD50 and LD90 of the extract of L. camara were significantly higher as compared to R. stricta, A. fruticosa, and R. chalepensis extract. The extract of L. camara also significantly reduced the activities of AChE and GST as compared to the larvae, treated with the extracts of another plant extracts as well as a positive control. The chemical composition of L. camara, was determined through GC–MS. Conclusions: The most important insecticidal compounds were including undecane, terephthalic acid, dimethyl-propane-thiosulfinate, fluorobenzoic acid octadecenoic acid. The insecticidal activity of the L. camara extracts against Cx. pipiens might be due to one or more of these compounds.